Screening and Selection for Physiological Characters Contributing to Salinity Tolerance in Rice - Duangjai Suriya-arunroj; Nopporn Supapoj; Apichart Vanavichit; Theerayut Toojinda (Agriculture and Natural Resources, 2005)
Two screening techniques, one initial screening using nutrient solution culture at young seedling stage and the other using soil in pots at vegetative stage, were used for identification of genotypes for salinity tolerance. Sixteen rice lines and cultivars were screened initially at seedling stage. Germinated seeds were placed on styrofoam plates floated on nutrient solution in a plastic container. After 14 days of sowing, the seedlings were subjected to salinization. The results showed that there were 3 groups of rice with different levels of response to salinity ; tolerant group consisted of Pokkali, FL496 and FL530, moderately tolerant group consisted of FL358, FL367, FL411, FL416, FL434, FL443, FL478, FL523, FL563, KMK and DDG, and susceptible group were KDML105 and RD6. To confirm the reliability of this initial screening technique, the visual salt-injury symptom was compared with the mean performance of salinity damage rating, Na+, K+ content and Na+/K+ absorption ratio in young leaves , old leaves and stem to identify physiological characters contributing to salinity tolerance in rice in the vegetative experiment. Eight lines/cultivars of rice were selected from the seedling screening to further investigate tolerant ability at vegetative stage in soil medium. In this test, 21 day-old seedling were subjected to 3 levels of salinity, 4,8 and 12 dS /m. The results showed visual scores to match with the Na+/K+ ratio, the cultivars with low Na+/K+ ratio had high tolerant ability and the susceptible one had high Na+/K+ ratio. The two selected salt tolerant recombinant inbred lines were FL496 and FL478 and two landrace cultivars selected were DDG and KMK which will be used as donors to introgress salt tolerant QTL into target cultivars (KDML105 and RD6) in salt tolerance breeding program.